Effect of Bio and chemical Fertilizers on some physiological traits and yield of Arugula - Ali, Kawa A.; Hamad, Hussain H.; Qadir, Shorsh Kh. (Sulaimani Journal for Pure and Applied Sciences, 2020)
A study was conducted in Erbil agricultural research directorate protected plastic tunnel to investigate the effect of five fertilization types; biofertilizer; locally prepared compost; manufactured compost; chemical fertilizer (DAP); and no fertilizer (control) on some physiological, yield traits of Arugula and some soil properties. Results indicated significant increase of green harvesting leaves dry weight in four cutting processes, leaf area, plant height, number of branches per plant, and chlorophyll content when arugula plants treated with different types of fertilizers compared to no fertilizer plots. Manufactured compost produced highestseed yield 1.98 (t. ha-1) comparing to other fertilizer treated plots and the lowest seed yield was 1.04 (t. ha-1) under no fertilization conditions. All yield component data revealed the positive effect of fertilization on arugula yield, straw and biological yield were at higher levels under local and manufactured compost as well as DAP fertilization treatments. The significant effect of fertilization enhanced chemical characteristics of arugula seeds data of nitrogen, phosphorus potassium, protein, oil percentage and poly phenol content comparing to no fertilizers treatment. Soil chemical characteristics were elevated after 45 days from finishing the study which insures the importance of organic fertilizers effect on soil and environment. Taste panel declare differences in leaf pungent taste, leaf texture and color according to fertilization type. Levels of positive effect of using fertilizers on fixed oil yield was from highest to lowest Manufactured compost, Local compost, DAP, Biofertilizer and no fertilizer (control).
Keywords: Biofertilizer; Chlorophyll; Fixed Oil Yield; Arugula